Conversion of supramolecular organic framework to uranyl-organic coordination complex: a new "matrix-free" strategy for highly efficient capture of uranium. Issue 15 (30th January 2017) - Li, Bo; Wang, Lei; Li, Yang; Wang, Dongqi; Wen, Rui; Guo, Xinghua; Li, Shoujian; Ma, Lijian; Tian, Yin
Abstract : Conversion of hydrogen-bonded supramolecular organic frameworks (HSOF) to a uranyl-organic coordination complex (UOCC) by uranyl-induced disassembly and reassembly: innovative "matrix-free" strategy for highly efficient uranium capture. Abstract : Herein, an innovative "matrix-free" strategy has been proposed for highly efficient uranium capture via uranyl-induced disassembly and reassembly of the two functional building blocks of the as-prepared hydrogen-bonded supramolecular organic framework (HSOF), which is composed of N-donor-containing melamine and O-donor-containing trimesic acid self-assembled through hydrogen bonding. The batch experimental results demonstrated that HSOF possesses excellent extraction capacity ( q m = 444 mg g −1 ), >99% removal efficiency in the range of tested U(vi ) concentration (20–130 ppm) with a considerably large K Ud value of 1.3 × 10 7 mL g −1 at 130 ppm, and very fast extraction rate (<10 min) for UO2 2+ . Especially, the uranium selectivity ( S U = q e-U / q e-tol ) of HSOF stays above 80% over the pH range tested in a uranium-containing solution with 11 competing cations, and distinctively, reaches the so far unreported 99% with a great capacity of 309 mg g −1 at pH 2.5. It is worth noting that a clear morphology transformation of HSOF nanowires to nanosheets of the uranyl-organic coordination complex (UOCC) after extraction has been observed only in the presence of uranyl ions. Moreover, according to experimental characterization and DFT studies, a possible mechanism for the efficient capture of uranium is proposed: the stronger coordination interaction among uranyl, TMA and MA could replace the weaker hydrogen-bond interaction originally linking the two building blocks in HSOF in the extraction process.